Comparison of the single breath with the intrabreath method for the measurement of the carbon monoxide transfer factor in subjects with and without airways obstruction. Issue 8 (August 1995) - Kiss, D; Popp, W; Wagner, C; Havelec, L; Sertl, K
Abstract : BACKGROUND–Measurement of the carbon monoxide transfer factor (TLCO) has traditionally been performed using the single breath method but recently the intrabreath method has been developed. The aim of this study was to compare the two methods in the clinical evaluation of patients with obstructive and non-obstructive pulmonary disorders. METHODS–Measurements of TLCO with the intrabreath method were carried out on a study sample composed of 50 patients with non-obstructive disorders and 50 with airways obstruction (FEV1/FVC < 70%) either before or after a single breath measurement of the TLCO had been performed. The method involves the continuous analysis of a single slow expirate using a computerised rapid multigas infrared analyser. TLCO, alveolar volume (VA), TLCO/VA, and inspired vital capacity (IVC) values were obtained for both groups by both methods. RESULTS–When measured with the intrabreath method the group with airways obstruction showed lower TLCO and TLCO/VA values than the non-obstructive group. VA was higher in both patient groups when measured with the intrabreath technique. The same test also showed higher TLCO values with the intrabreath method in the group with non-obstructive disorders and lower TLCO/VA values with the intrabreath method in those with airways obstruction. The corresponding parameters obtained by the two methods correlated closely, with no correlation between the magnitude of the differences with the magnitude of the readings. An index of gas mixing indicated a better distribution of the inspired air for the intrabreath method than for the single breath method. The VA values obtained with the intrabreath method showed a closer agreement to the actual total lung capacities measured by body plethysmography. CONCLUSION–The intrabreath method of determining TLCO is comparable to the traditional single breath method. Measurement of alveolar volume by the intrabreath method approximates more closely to total lung capacity, even in subjects with airways obstruction.